OPTIMALISASI PENGELOLAAN KEUANGAN BUMDES MELALUI PENERAPAN SISTEM INFORMASI KEUANGAN - Lilis Karlina; Meta Nursita; Fina Fitriyani; Lina Rahmawati; Siti Aisyah Rianti (Publika Citra Media, 2026)
Financial management plays an important role in supporting the sustainability and development of Village-Owned Enterprises (BUMDes). However, many BUMDes still face problems related to manual financial recording, limited accounting knowledge, and low utilization of information technology. This Community Service Program (Pengabdian Kepada Masyarakat/PKM) aims to optimize BUMDes financial management through the implementation of a digital-based financial information system. The methods used in this program include counseling, training, simulation, and direct assistance for BUMDes administrators. The results of the activity indicate an improvement in participants’ understanding of basic accounting concepts and the use of financial information systems for recording transactions and preparing financial reports. The implementation of the financial information system has proven to improve efficiency, accuracy, transparency, and accountability in BUMDes financial management. Therefore, the digitalization of financial systems can serve as a strategic solution to strengthen financial governance and support sustainable village economic development.